2022
DOI: 10.1039/d2py00748g
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced oxygen-catalyzed RAFT polymerization using heterogeneous bionic enzymes

Abstract: Exploiting aerobic polymerization approaches is the feasible strategy to fundamentally address the phenomenon of oxygen blocking polymerization. A photo-bionic enzyme-reversible addition-fragmentation chain transfer (RAFT) polymerization system (COF/H2O/O2) was successfully constructed,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…To further visualize the intrinsic association of the COF-dominant “oxygen-/water-fueled” PET-RAFT protocol, we performed a controlled analysis of key active species upon each other. The UV–vis spectra of benzoquinone (BQ) (Figures a and S17, S18) recorded a gradual decrease of the characteristic absorption peak with increasing light exposure time, corroborating the suitable reduction potential of the COFs . The comparison shows that with the addition of TEA, the items showed a faster decrease in frequency.…”
Section: Resultsmentioning
confidence: 58%
See 3 more Smart Citations
“…To further visualize the intrinsic association of the COF-dominant “oxygen-/water-fueled” PET-RAFT protocol, we performed a controlled analysis of key active species upon each other. The UV–vis spectra of benzoquinone (BQ) (Figures a and S17, S18) recorded a gradual decrease of the characteristic absorption peak with increasing light exposure time, corroborating the suitable reduction potential of the COFs . The comparison shows that with the addition of TEA, the items showed a faster decrease in frequency.…”
Section: Resultsmentioning
confidence: 58%
“…The UV−vis spectra of benzoquinone (BQ) (Figures 6a and S17, S18) recorded a gradual decrease of the characteristic absorption peak with increasing light exposure time, corroborating the suitable reduction potential of the COFs. 30 The comparison shows that with the addition of TEA, the items showed a faster decrease in frequency. TEA acts as an electron sacrificial agent mainly to trap holes and reduce the recombination efficiency between charge and holes, allowing more photogenerated electrons to come into contact with oxygen.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Very recently, Hou, Xiao, Zhao, and coworkers reported that 1,3,6,8-tetrakis(4-formylphenyl)pyrene (TFPPy)-azine based covalent organic frameworks (COFs) generated initiating hydroxyl radicals from water and atmospheric air under white light irradiation (15 mW cm À2 ). 172 Photoinduced production of the superoxide radical anion followed by reaction with water generated hydroxyl radicals. Thus, in a completely open vial, the polymerization rate increased with an increase in the volumetric ratio of water to dioxane, whereas polymerization did not proceed in the absence of water.…”
Section: Gibson and Coworkers Disregarded The High Dispersities Ofmentioning
confidence: 99%